PENGARUH GENOTIP DAN PUPUK DAUN TERHADAP PERTUMBUHAN DAN PRODUKSI KEDELAI PANEN MUDA PADA BUDIDAYA JENUH AIR (The Effect of Genotype and Foliar Fertilizer on the Growth and Production of Fresh Soybean under Saturated Soil Culture) - Ghulamahdi, Munif (Universitas Palangka Raya, 2008)
ABSTRACTThe objective of this experiment was to determine of foliar fertilizer concentration on twosoybean genotypes under saturated soil culture. The experiment was conducted in IPB ExperimentalStation Cikarawang, Bogor, from February to May 2000. This experiment used split plot design withthree replication. The mainplot was genotypes consisted of : NS (Nakorn Sawan), and G (Genotype)10428; and the subplot was foliar fertilizer concentration consisted of : 0, 2, 4, 6, 8 g L-1 water. Thegenotype effected to the root dry weight at 8 WAP (Week After Planting), stalk and leaf dry weight at6 WAP, and biomass fresh weight per plot. The growth of G 10428 was higher than NS. The foliarfertilizer concentration only effected to the biomass fresh weight per plot, and the interaction did noteffect to the all variables. The highest biomass fresh weight was obtained on 6 g L-1 water.Key Word :Soybean, genotype, foliar fertilizer and saturated soil culture